Xylochrysis aquatica sp. nov. (Woswasiaceae) from freshwater habitats in Sichuan Province, China - Song, Jing-Yi; Yang, Yi; Yu, Xian-Dong; Dissanayake, Asha J.; Tian, Qing (Phytotaxa, 2023)
During surveys of ascomycetous fungi in Sichuan province, China, a new aquicolous taxon, Xylochrysis aquatica, isolated from a decaying trunk of an undetermined wood is described. Xylochrysis aquatica differs from the type species X. lucida in having solitary, smaller ascomata with a short papillate ostiole, without a golden yellow layer of surrounded cells and larger asci with rounded ascospores. The phylogenetic analysis of the combined ITS-LSU-SSU-rpb2-tef1-α sequence data matrix showed that X. aquatica clustered together with X. lucida and formed as different lineages, it can be recognized as a distinct species. A detailed description and an illustration of the novel species are given while a nucleotide comparison of related species is provided.